2022
DOI: 10.1159/000525133
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Cardiovascular Medications in Neonatal Hypotension

Abstract: <b><i>Background:</i></b> Comparative studies among the various cardiovascular medications used for the treatment of neonatal hypotension are lacking. <b><i>Methods:</i></b> This systematic review and pairwise meta-analysis of the anti-hypotensive treatments in preterm and term infants was conducted to evaluate efficacy and impact on outcome. Electronic databases were searched up to February 2021 for relevant articles. As an extension of the current approach for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Moreover, DOP, but not DOB, was associated with suppression of TSH, T4, and prolactin that was reversed soon after treatment stopped [116]. These findings were confirmed by systematic reviews and meta-analyses that regarded existing data insufficient to support a definite suggestion, mainly due to sparse data on the long-term ND effects [16,61].…”
Section: Comparisons Between Anti-hypotensive Medicationsmentioning
confidence: 66%
See 1 more Smart Citation
“…Moreover, DOP, but not DOB, was associated with suppression of TSH, T4, and prolactin that was reversed soon after treatment stopped [116]. These findings were confirmed by systematic reviews and meta-analyses that regarded existing data insufficient to support a definite suggestion, mainly due to sparse data on the long-term ND effects [16,61].…”
Section: Comparisons Between Anti-hypotensive Medicationsmentioning
confidence: 66%
“…Two early studies comparing DOP with placebo (dextrose in water) or volume expansion (using plasma protein fraction) in 14 severely asphyxiated term neonates and 39 hypotensive VLBWI, respectively, showed that DOP was more effective in increasing AP and improving echocardiographic indices without any significant change in HR or systolic time intervals [209,227]. These findings were confirmed by systematic reviews [61,232]. Dopamine vs. dobutamine.…”
Section: Comparisons Between Anti-hypotensive Medicationsmentioning
confidence: 88%
“…[19][20][21] There are three systematic reviews published until now on the efficacy of different inotropes in preterm neonates with shock. [22][23][24] Outcomes (O): The primary outcomes were mortality and major brain injury (MBI) (intraventricular haemorrhage >grade 2 or cystic periventricular leukomalacia). Secondary outcomes included response to treatment and NEC ≥stage 2.…”
Section: Introductionmentioning
confidence: 99%
“… 22 23 Sarafidis et al compared different inotropes in preterm neonates with shock in pairwise meta-analyses. 24 Most of the aforementioned systematic reviews included neonates with shock of varying aetiopathogenesis. Henceforth, we undertook this systematic review and network meta-analysis (NMA) with an aim to study the efficacy and safety of various interventions in preterm neonates with probable TCI.…”
Section: Introductionmentioning
confidence: 99%
“…This could justify the slight decrease in the use of inotropes observed overtime (from 2009-2013 to 2014-2015) [10]. Nevertheless, irrespective of the existing controversy surrounding the definition of AH in neonates, and the lack of randomized clinical trials (RCTs) [11], inotropes are still given in a considerable proportion of preterm infants. Published data from the US and Norway show that the rate of inotrope administration to NICU patients ranges between 2.7% and 25%, depending on gestational age (GA) [12,13].…”
Section: Introductionmentioning
confidence: 99%